Opportunities and Challenges of Nanoparticles in Digestive Tumours as Anti-Angiogenic Therapies - Yang, Zhengyang; Deng, Wei; Zhang, Xiao; An, Yongbo; Liu, Yishan; Yao, Hongwei; Zhang, Zhongtao (Frontiers in Oncology, 2022)
Digestive tumours, a common kind of malignancy worldwide, have recently led to the most tumour-related deaths. Angiogenesis, the process of forming novel blood vessels from pre-existing vessels, is involved in various physiological and pathological processes in the body. Many studies suggest that abnormal angiogenesis plays an important role in the growth, progression, and metastasis of digestive tumours. Therefore, anti-angiogenic therapy is considered a promising target for improving therapeutic efficacy. Traditional strategies such as bevacizumab and regorafenib can target and block the activity of proangiogenic factors to treat digestive tumours. However, due to resistance and some limitations, such as poor pharmacokinetics, their efficacy is not always satisfactory. In recent years, nanotechnology-based anti-angiogenic therapies have emerged as a new way to treat digestive tumours. Compared with commonly used drugs, nanoparticles show great potential in tumour targeted delivery, controlled drug release, prolonged cycle time, and increased drug bioavailability. Therefore, anti-angiogenic nanoparticles may be an effective complementary therapy to treat digestive tumours. In this review, we outline the different mechanisms of angiogenesis, the effects of nanoparticles on angiogenesis, and their biomedical applications in various kinds of digestive tumours. In addition, the opportunities and challenges are briefly discussed.